2022
DOI: 10.3389/fpls.2022.969343
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of plant cell wall surveillance in response to pathogens, cell wall-derived ligands and the effect of expansins to infection resistance or susceptibility

Abstract: Cell wall integrity is tightly regulated and maintained given that non-physiological modification of cell walls could render plants vulnerable to biotic and/or abiotic stresses. Expansins are plant cell wall-modifying proteins active during many developmental and physiological processes, but they can also be produced by bacteria and fungi during interaction with plant hosts. Cell wall alteration brought about by ectopic expression, overexpression, or exogenous addition of expansins from either eukaryote or pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 166 publications
0
8
0
Order By: Relevance
“…In our experiment, we observed cell wall and structure-related proteins being up-regulated, cell wall structural protein being significantly downregulated. This could suggest that the lack of the glycine-rich protein or overexpression of the expansin and hydrolase proteins could be responsible for the brittle-nature of HLVd infected plants (22). Similarly, it has been reported that plants infected with HLVd have also been known to be less vigorous and carry an altered internode length compared to uninfected clones of the same cultivar (9), (23).…”
Section: Discussionmentioning
confidence: 99%
“…In our experiment, we observed cell wall and structure-related proteins being up-regulated, cell wall structural protein being significantly downregulated. This could suggest that the lack of the glycine-rich protein or overexpression of the expansin and hydrolase proteins could be responsible for the brittle-nature of HLVd infected plants (22). Similarly, it has been reported that plants infected with HLVd have also been known to be less vigorous and carry an altered internode length compared to uninfected clones of the same cultivar (9), (23).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, very few reports showed the involvement of α-Expansins in both compatible and incompatible plant-microbe interactions [ 35 , 72 76 ]. Recently, some studies also demonstrated the putative role of the Expansin superfamily in mediating resistance responses to simultaneous abiotic and biotic stresses (cross-stress) as well as in defense priming processes and stress memory [ 35 , 77 81 ]. Our findings support those studies by showing that AdEXPA24 overexpression improves resistance against Meloidogyne sp.…”
Section: Discussionmentioning
confidence: 99%
“…below). The microbial enzymes are involved in establishing beneficial symbiotic interactions, virulence, or generation of short-chain sugar molecules for microbial digestion [ 80 , 81 , 82 , 83 , 84 ]. They have their own evolutionary history and adaptation mechanism to their hosts.…”
Section: Polysaccharide Degradationmentioning
confidence: 99%